Below or all the way to the peak? Oxygen uptake efficiency slope as the index of cardiorespiratory response to exercise - the NOODLE study - Kasiak, P.; Kowalski, T.; Rebis, K.; Klusiewicz, A.; Starczewski, M.; Ladyga, M.; Wiecha, S.; Barylski, M.; Poliwczak, A. R.; Wierzbinski, P.; Mamcarz, A.; Sliz, D. (Frontiers in Physiology, 2024)
Background: The ratio of oxygen uptake (VO2) to minute ventilation (VE) is described as the oxygen uptake efficiency slope (OUES). OUES has been suggested as a valuable submaximal cardiorespiratory index; however, its characteristics in endurance athletes remain unknown. In this study, we a) investigated OUES between different time intervals, b) assessed their prediction power for VO2peak, and c) derived new prediction equations for OUES tailored for well-trained individuals.